Multiplicity of registration systems: multiplicity of research strategies - Mbele, Nomamfengu (University of the Witwatersrand, School of Architecture and Planning, 2017)
This research is about assessing the registration policy instrument utilised by various street trader management stakeholders. The research focuses on how the street traders experience these registration systems in the current street trader management context. Taking on the phenomenological qualitative research approach, the research tells the stories of registration, as told by street traders in and around Noord Street linear markets. This will be used as an attempt to explore and document the otherwise messily understood registration systems. The dominant and formalised municipal registration systems are plagued by the inconsistency, fragmentation and unilateral decision making which has contributed to restrictive, yet more importantly the disempowerment of street traders. Whilst the informal civil-society registrations is characterised by collective, unifying and effective practices that have given the street traders an element of empowerment, yet there is still an urge to establish a management tool that would give the traders comprehensive empowerment to deconstruct the unequal power relations that persist in the South African society.
A dissertation submitted to the School of Architecture and Planning, University of the Witwatersrand, in fulfillment of the requirements for the Bachelor of Science with Honours in Urban and Regional Planning.
Keywords: Street trader management; Registration policy; Linear markets--South Africa--Johannesburg--Noord Street; Street traders experiences; Traders comprehensive empowerment